Understanding Indonesian Learners’ Affective Profiles in English Language Acquisition: A Literature Review - Marcha Stephanie Inapratama Matitaputty (P3M Politeknik Negeri Ambon, 2023)
This study investigates the affective dimensions—motivation, language anxiety, attitudes, and self-efficacy—that influence English language acquisition among Indonesian learners. Drawing upon 42 peer-reviewed studies published between 2018 and 2022, the study contextualizes these affective variables within Indonesia’s sociocultural and educational landscape, including the contrasting impacts of Kurikulum 2013 and Kurikulum Merdeka. Findings reveal that motivation—especially intrinsic and integrative forms—is the most consistent predictor of success, yet it is often undermined by exam-driven instruction and rigid pedagogies. Language anxiety, primarily linked to fear of mistakes and negative evaluation, remains a critical barrier, especially in speaking tasks. Attitudes toward English are increasingly positive in urban and multicultural regions, yet ambivalence persists in rural areas due to cultural dissonance. Self-efficacy, shaped by prior experiences, teacher support, and school type, significantly affects learners' confidence and risk-taking behavior. The study highlights the dynamic interplay among these variables and calls for affect-aware pedagogy. Recommendations include curriculum reform, teacher training, inclusive classroom practices, and expanded support for under-resourced schools. By integrating affective goals into language policy and instruction, Indonesian ELT can better support learners’ emotional readiness and long-term success. Keywords: Affective factors, motivation, language anxiety, attitudes, self-efficacy, English language acquisition, Indonesian EFL learners, Kurikulum Merdeka,